EFEKTIFITAS MOTIVASI KERJA TENAGA KESEHATAN RUMAH SAKIT - Singgih Tiwut Atmojo; Melly Melly (Universitas Tanjungpura, 2021)
The purpose of this research is to determine the influence of hygiene factors and motivational factors that can encourage health workers to work more productively at the Hospital of St. Vincentius Singkawang. Sources of data obtained from observations and questionnaires. The data analysis method used in this study is a qualitative method with descriptive statistical data analysis techniques. The population of this research is 118 Vincentius Singkawang Hospital health workers. The sampling technique uses probability sampling. From the results of the analysis, the authors conclude that the leadership has fulfilled the factors of workforce motivation in accordance with financial capabilities. However, there are still factors that have not been well paid attention to is the salary given by the hospital to employees must contain the principle of fairness and refer to the legislation. So that the organization will obtain, maintain, and employ a number of employees with a variety of positive attitudes and behaviors, productive performance, effective and efficient in completing work for the interests of the organization in order to achieve the goals of the St. Vincentius Hospital Singkawang.Keyword: Motivational Factor, Hygine Factor